"{d^2y\\over dx^2}-{1\\over x}\\cdot{dy\\over dx}-4x^2y=8x^2\\sin x^2"
Here
"P=-\\dfrac{1}{x},"
"Q=-4x^2,"
"R=8x^2\\sin x^2"
Changing the independent variable from "x" to "z"
"{d^2y\\over dz^2}+P_1{dy\\over dz}+Q_1y=R_1"where
"Q_1=\\dfrac{Q}{({dz\\over dx})^2}"
"R_1=\\dfrac{R}{({dz\\over dx})^2}"
We choose "z" such that
Let
Then
integrating
We have
"P_1=\\dfrac{{d^2z\\over dx^2}+P{dz\\over dx}}{({dz\\over dx})^2}=\\dfrac{2+(-\\dfrac{1}{x})(2x)}{(2)^2}=0"
"R_1=\\dfrac{R}{({dz\\over dx})^2}=\\dfrac{8x^2\\sin x^2}{(2x)^2}=2\\sin z"
"{d^2y\\over dz^2}-y=2\\sin z"
Method of undetermined coefficients
Homogeneous second order differentional equation
Characteristic equation
The general solution of the homogeneous differential equation is
Let "Y=A\\cos z+B\\sin z," then
"{d^2Y\\over dz^2}=-A\\cos z-B\\sin z"
"A\\cos z+B\\sin z+A\\cos z+B\\sin z=2\\sin z"
"A=0"
"B=1"
The general solution of the nonhomogeneous equation
"y(z)=C_1e^{-z}+C_2e^{z}+\\sin z"
Substitute "z=x^2" and obtain the general solution
Comments
Dear Renu Chaturvedi, thank you for correcting us.
After changing the variable the differentiation of y" = 2 dy/dt + 4x^2 d^2y/dt^2 but u have written y" = (2/x) dy/dt + 4x d^2y/dt^2 how??
Leave a comment